Judges, justice, and public power: the constitution and the rule of law in South Africa. (2nd January 2018) - Cameron, Edwin
ABSTRACT: This is the text of the High Court of Australia's annual lecture delivered at the High Court of Australia on 11 October 2017. The lecture critiques 'legalism', the denial of personal choice or value judgment in adjudication. It discusses the impact of legalism in apartheid South Africa and Australia, and the break with legalism effected by South Africa's new Constitution. The lecture is reproduced here with the kind permission of its organiser, Justice James Edelman.